Universal screening for developmental dysplasia of the hip in Austria: what have we learned? - Tanja Kraus; Catharina Chiari (Exploration of Musculoskeletal Diseases)
Hip ultrasound, according to Graf, is a standardized sonographic method for the detection of developmental dysplasia of the hip (DDH) during the neonatal period. Graf established his method during the 1980s in his home country Austria. It was implemented in the Austrian Mother-Child Health Passport in 1992. Since then it served as a general screening method. The aim of this paper is to present the effects of general hip ultrasound screening in Austria by reviewing and analysing the literature of Austrian authors. This article described how the method was further developed and which prerequisites are currently required for a correct diagnosis. Moreover, it reports about the education in ultrasound screening according to Graf in Austria.